MODEL PEMBERDAYAAN MASYARAKAT BANYUASIN MELALUI BIMBINGAN MANDIRI DALAM INSTALASI JARINGAN LAN UNTUK MENDUKUNG AKSES INFORMASI - Taramita, Sela; Qisthiano, M Riski (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to design and implement a community empowerment model in Banyuasin Regency through self-guided training in Local Area Network (LAN) installation to enhance independent and sustainable access to information. The lack of public understanding of networking technology and limited access to digital resources serve as the background for initiating a needs-based training approach. The method employed is a participatory approach involving technical workshops, field assistance, and post-training competency evaluations. The results show that self-guided training significantly improves participants' knowledge, skills, and independence in building and managing basic LAN infrastructure in their local environments. Consequently, the community gains easier access to educational resources, public services, and digital-based economic opportunities. This model can be replicated in other regions with similar conditions as a strategy for technology-based empowerment